Evaluating the impact of land use and land cover changes on forest ecosystem service values using landsat dataset in the Atwima Nwabiagya North, Ghana - Richard Baidoo; Kwame Obeng (Heliyon, 2023)
This study investigated land use and land cover (LULC) changes and its impact on forest ecosystem service values for 20 years in the Atwima Nwabaiagya North District using Landsat images of 2002, 2012 and 2022. Supervised classification with Maximum Likelihood Algorithm was used to classify the Landsat images. Five LULC types (high-dense forest, low-dense forest, water, bare-ground, and Built-up area) were successfully classified, with overall accuracies of 99.0 % and Kappa coefficients of 0.99. The result of the study showed a reduction of high-dense forest to 23.87 %, low-dense forest to 26.53 %, and water areas as 1.16 % whereas built-up (21.44 %) and bare-ground (27 %) experienced an expansion in their land areas. Related literatures and ecological assets value table with adjusted price value were used to evaluate ecosystem service values in response to LULC changes. The study discovered that ecosystem service value for high and low-dense forests have declined from USD 22.68 million and USD 8.75 million to USD 14.56 million and USD 5.2 million respectively. The overall total ecosystem service value declined by USD 33.73 million in 2002 to USD 21.91 million in 2022. It was revealed that the most notable feature to changes in forest ecosystem service values was the expansion of built-up and bare-grounds. There is a need to curb the current drivers of LULC changes in the Atwima Nwabiagya North to stop further forest degradation for optimum delivery of forest ecosystem service values in the district. For land use planners and decision makers who need site-specific information on the effects of LULC alterations on values of forest ecosystem services, the study's findings are essential. This will make it easier to track past environmental changes and obtain quick, accurate results for use in decision-making.